Pelatihan Manajemen Bandwith Di SMA Amir Hamzah - Tommy Tommy; Rosyidah Siregar; Imran Lubis; Andi Marwan Elhanafi; Ruswan Nurmadi (Jurnal Pengabdian Kepada Masyarakat Digital, 2022)
The need for Internet access today is very important. The Internet was a good alternative for finding the latest information, articles, and knowledge. Bandwidth sharing or bandwidth management using a mikrotik router on each host/user is an important part for internet service providers to do. Amir Hamzah High School (SMA) is one of the high schools located in the city of Medan. High school in Indonesia today requires skills in the field of networking. Which bandwidth management divides the network quota either at school or in other public places. Bandwidth is the most important part of a network, therefore bandwidth or bandwidth management is very much taken into account in order to create fast and flexible access in order to maximize internet connection according to the needs in each section, it is necessary to have bandwidth management to share the amount of bandwidth needed. bandwidth management is very easy and efficient to be used by every internet service provider because by using bandwidth each host/user will get bandwidth with the same level or size without disturbing the bandwidth of other users/hosts. This activity is an activity that aims to provide basic bandwidth management training to Amir Hamzah High School students where based on the activities that have been carried out, it was found that 44% of students could apply the training material very well while the other 56% could only apply part of the material presented.Keywords: Community Service, Network, Bandwidth, Mikrotik, Highschool